2021
DOI: 10.33314/jnhrc.v18i4.2939
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Accuracy of Blumensaat Line Angle and Its Apex along with Anterior Cruciate Ligament Inclination Angle for Diagnosis of Anterior Cruciate Ligament Tear with Abundant Remnant

Abstract: Background: Anterior Cruciate Ligament Blumensaat line angle and Anterior Cruciate Ligament Inclination angle can be measured when Anterior Cruciate Ligament is visualized on Magnetic Resonance Imaging. Both these angles can be helpful to determine the intactness of Anterior Cruciate Ligament. The aim of this study was to evaluate the diagnostic accuracy of Anterior Cruciate Ligament - Blumensaat line angle, apex of Anterior Cruciate Ligament - Blumensaat line angle and Anterior Cruciate Ligament - Inclination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[ 16 , 29 ] Sauer et al[ 29 ] reported that individuals with ACL injury had a high beta angle, while the alpha angle has not been found a predisposing factor for ACL injury. [ 16 ] However, to the best of our knowledge, there is only one prospective study investigating whether ACLIA is a risk factor for ACL injuries, in which Adhikari et al[ 30 ] found ACLIA and BA to be sensitive and specific for ACL injury. Our results suggest that one of the main risk factors for ACL injury can be small ACLIA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 29 ] Sauer et al[ 29 ] reported that individuals with ACL injury had a high beta angle, while the alpha angle has not been found a predisposing factor for ACL injury. [ 16 ] However, to the best of our knowledge, there is only one prospective study investigating whether ACLIA is a risk factor for ACL injuries, in which Adhikari et al[ 30 ] found ACLIA and BA to be sensitive and specific for ACL injury. Our results suggest that one of the main risk factors for ACL injury can be small ACLIA.…”
Section: Discussionmentioning
confidence: 99%